MTSS1 is downregulated in nasopharyngeal carcinoma (NPC) which disrupts adherens junctions leading to enhanced cell migration and invasion - Zheng, Shixing; Wang, Xiaoxia; Matskova, Liudmila; Zhou, Xiaoying; Zhang, Zhe; Kashuba, Elena; Ernberg, Ingemar; Aspenström, Pontus (Frontiers in Cell and Developmental Biology, 2023)
Loss of cell–cell adhesions is the indispensable first step for cancer cells to depart from the primary tumor mass to metastasize. Metastasis suppressor 1 (MTSS1) is frequently lost in metastatic tissues, correlating to advanced tumor stages and poor prognosis across a variety of cancers. Here we explore the anti-metastatic mechanisms of MTSS1, which have not been well understood. We found that MTSS1 is down regulated in NPC tissues. Lower levels of MTSS1 expression correlate to worse prognosis. We show that MTSS1 suppresses NPC cell migration and invasion in vitro through cytoskeletal remodeling at cell–cell borders and assembly of E-cadherin/β-catenin/F-actin in adherens junctions. The I-BAR domain of MTSS1 was both necessary and sufficient to restore this formation of E-cadherin/β-catenin/F-actin–mediated cell adherens junctions.